Misuse of Financial Services for the Sexual Exploitation of Children: A Socio-Legal Study in Indonesia - Sofian, Ahmad (UI Scholars Hub, 2025)
This paper discusses children in the online space who are entrapped in interactions across various social media applications and digital platforms and became victims of sexual exploitation practices and how this sexual exploitation is facilitated by the availability of diverse financial service providers that allow for transactions between perpetrators and victims as well as distributors and producers. In view of ongoing efforts by the Indonesian government to formulate more relevant and effective regulations for child protection, this study is crucial for our understanding of the realities of sexual exploitation in the context of children’s use of social media and may contribute to the design of a legal framework for child protection which can better safeguard children from sexual exploitation. This research employs a socio-legal approach, combining in-depth interviews and legal document analysis in exploring the role of financial services in facilitating transactions between perpetrators of sexual exploitation and children in the online realm. We found that sexual exploitation of children in Indonesia takes place through diverse means: by Video Call Sexual (VCS) activties, live streaming of sexual content, grooming, online coercion to produce child sexually explicit material and pornography, and the distribution of Child Sexual Violence Material (CSVM). In many cases financial payments are received as compensation for the procuction of sexually explicit material. The financial service applications used encompass cross-border financing, digital wallets, payment applications, banking applications, digital banking applications, cryptocurrencies, and even online game top-up gifts. This study recommends the Government of Indonesia to raise awareness among financial service providers of their role in facilitating financing of child sexual exploitation, and to strengthen collaboration with Public-Private Partnership forums in developing tracking and monitoring mechanisms. Dialogue between the Government of Indonesia, the House of Representatives, financial service institutions, the Financial Services Authority, the Financial Transaction Reports and Analysis Centre, and other civil society organizations is essential to protect children from sexual abuse which is facilitated by children’s access to digital financial services.